Bat and the end of everything - Arnold, Elana K.; Santoso, Charles (New York : Walden Pond Press, 2019)
Bat grows anxious as his third-grade year comes to an end and the time to release his pet skunk, Thor, out into the wild approaches.
800L
3-6
5.8
Some copies purchased with funds from an OASL Connie Hull Mini-Grant, Mt. View 2024
Keywords: Autism -- Fiction; Skunks as pets -- Fiction; Wildlife rescue -- Fiction; Family life -- Fiction